Adolescent Metabolic Syndrome Risk Is Increased with Higher Infancy Weight Gain and Decreased with Longer Breast Feeding - Kim Khuc; Estela Blanco; Raquel Burrows; Marcela Reyes; Marcela Castillo; Betsy Lozoff; Sheila Gahagan (International Journal of Pediatrics)
Background. Prevalence of the metabolic syndrome is increasing in pediatric age groups worldwide. Meeting the criteria for the metabolic syndrome puts children at risk for later cardiovascular and metabolic disease. Methods. Using linear regression, we examined the association between infant weight gain from birth to 3 months and risk for the metabolic syndrome among 16- to 17-year-old Chilean adolescents (n=357), accounting for the extent of breastfeeding in infancy and known covariates including gender, birth weight, and socioeconomic status. Results. Participants were approximately half male (51%), born at 40 weeks of gestation weighing 3.5 kg, and 48% were exclusively breastfed for ≥90 days. Factors independently associated with increased risk of metabolic syndrome in adolescence were faster weight gain in the first 3 months of life (B=0.16, P<0.05) and male gender (B=0.24, P<0.05). Breastfeeding as the sole source of milk for ≥90 days was associated with significantly decreased risk of metabolic syndrome (B=−0.16). Conclusion. This study adds to current knowledge about early infant growth and breastfeeding and their long-term health effects.